2019
DOI: 10.1002/tafs.10170
|View full text |Cite
|
Sign up to set email alerts
|

Growth, Condition, and Trophic Relations of Stocked Trout in Southern Appalachian Mountain Streams

Abstract: Stream trout fisheries are among the most popular and valuable in the United States, but many are dependent on hatcheries to sustain fishing and harvest. Thus, understanding the ecology of hatchery‐reared trout stocked in natural environments is fundamental to management. We evaluated the growth, condition, and trophic relations of Brook Trout Salvelinus fontinalis, Brown Trout Salmo trutta, and Rainbow Trout Oncorhynchus mykiss that were stocked in southern Appalachian Mountain streams in western North Caroli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 48 publications
(95 reference statements)
0
5
0
Order By: Relevance
“…Our DNA‐based analysis, in its current form, can only provide presence/absence assessments of prey composition due to inherent stochasticity stemming from DNA extraction, amplification, and high‐throughput sequencing (Piñol et al., 2018). Therefore, if researchers wish to acquire the most comprehensive insights possible, they should supplement the findings from DNA‐based methods with those stemming from quantitative methods, such as morphologic or isotopic characterisation (Fischer et al., 2019). Second, the taxonomic breadth of DNA‐based analyses is limited by both the barcoding primers used in the study as well as the completeness of the prey species reference database.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our DNA‐based analysis, in its current form, can only provide presence/absence assessments of prey composition due to inherent stochasticity stemming from DNA extraction, amplification, and high‐throughput sequencing (Piñol et al., 2018). Therefore, if researchers wish to acquire the most comprehensive insights possible, they should supplement the findings from DNA‐based methods with those stemming from quantitative methods, such as morphologic or isotopic characterisation (Fischer et al., 2019). Second, the taxonomic breadth of DNA‐based analyses is limited by both the barcoding primers used in the study as well as the completeness of the prey species reference database.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work at other sites has suggested that interspecific trophic competition with introduced salmonids, such as brown trout ( Salmo trutta ; Dewald & Wilzbach, 1992) and rainbow trout ( Oncorhynchus mykiss; Larson & Moore, 1985) may play a role in the extirpation of brook trout populations. However, studies that have investigated the feeding ecology of native brook trout coexisting with introduced brown and rainbow trout have either not documented the natural dietary composition of these species (Dewald & Wilzbach, 1992; Fausch & White, 1981; Larson & Moore, 1985) or have relied almost entirely upon morphological identification of digested prey to provide broad taxonomic classifications (Cunjak & Power, 1987; Fischer et al., 2019; Tebo & Hassler, 1963). To provide a more taxonomically‐precise classification for these trout species and to demonstrate the feasibility of DNA‐based dietary characterisations for other freshwater fish taxa, we performed DNA metabarcoding on gastric lavage samples collected from a stable, syntopic community of native brook trout, naturalised brown trout, and naturalised rainbow trout on the Laurel Ridge of Western Pennsylvania.…”
Section: Introductionmentioning
confidence: 99%
“…Interbreeding between the historical groups was marginal, except for 2001E and F. Previous studies in salmonids found similarly low introgression levels from domestic fish into the native population 61 , 62 . Potential causes include both lower rates of survival and reproduction and changes in the timing of maturity and spawning introduced by captive-breeding programs 11 , 63 67 . Shifted spawning timing may also contribute to non-random mating or reproductive isolation by time (temporal assortative mating; 68 ), resulting in low admixture with wild populations 64 .…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, genetic effects seem to be present even in F2 generation specimens that have lived their entire lives in natural environments 11 . Further, mortality rates may be higher in captivity-bred than wild fish because of less efficient foraging behaviour, leading to smaller body sizes and poor physical condition, and more risk-prone or exploratory behaviour that may result in higher predation and angling pressure 67 . The progeny of hatchery-raised trout may potentially also suffer from fewer resources at egg hatching in the wild, as early juvenile survival is positively correlated to egg size.…”
Section: Discussionmentioning
confidence: 99%
“…Different DNA methylation patterns have been observed in the sperm of captive-reared Atlantic salmon (Salmo salar) when compared with wild-born ones (Barreto et al, 2019). The above DNA and DNA methylation changes may result in phenotypic changes (e.g., body shapes: see Fragkoulis et al, 2017;Sánchez-González and Nicieza, 2017), as well as adaptive changes (e.g., survival: see Stoner and Davis, 1994; the returned number for spawning: see Jonsson et al, 2019;reproductive success: see Janowitz-Koch et al, 2019; empty stomach rate: see Fischer et al, 2019; food items: see Davis et al, 2018) in hatchery-reared seed stocks, in comparison to their wild counterparts (Kitada, 2020). Consequently, continuous hatchery stocking allows introgression with the wild gene pool or even the replacement of wild genes, which causes a decline in adaptation and a decrease in the production of post-mixed wild populations when stock enhancement programs are undertaken (Jonsson et al, 2019).…”
Section: Introductionmentioning
confidence: 99%